2022
DOI: 10.3389/fimmu.2022.811045
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 Levels in Idiopathic Inflammatory Myopathies and Their Association With Muscle Involvement and Disease Activity: A Cross-Sectional and Longitudinal Study

Abstract: BackgroundHeat shock proteins (Hsp) are chaperones playing essential roles in skeletal muscle physiology, adaptation to exercise or stress, and activation of inflammatory cells. We aimed to assess Hsp90 in patients with idiopathic inflammatory myopathies (IIM) and its association with IIM-related features.MethodsHsp90 plasma levels were analyzed in a cross-sectional cohort (277 IIM patients and 157 healthy controls [HC]) and two longitudinal cohorts to assess the effect of standard-of-care pharmacotherapy (n=3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…In the IG, we observed a significant improvement ( p < 0.05 in all) in muscle strength by 26% from baseline (assessed by MMT-8), endurance by 135% from baseline (assessed by FI-2), stability by 11% from baseline (assessed by FVA), and reduced disability by 39% from baseline (assessed by HAQ), which was clinically meaningful in a substantial proportion of patients [ 31 ]. In contrast to another recent study from our group where we described a significant decrease in plasma levels of Hsp90 from baseline to 24 weeks in the CG (baseline: 15.7 [9.8–29.5], week 24: 12.9 [9.7–16.6] ng/mL, p = 0.042) [ 20 ], in the present study we observed a stabilization of the plasma Hsp90 levels over 24 weeks in the IG (baseline: 12.5 [8.9–16.8], week 24: 12.0 [8.0–16.1] ng/mL, p = 0.969; difference between IG and CG: p = 0.014) ( Figure 1 A). Of particular interest, the change in plasma Hsp90 in the IG over the first 12 weeks was able to predict the improvement in muscle endurance (FI-2) over the entire 24-week intervention period (r = 0.510, p = 0.008) ( Figure 1 B).…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…In the IG, we observed a significant improvement ( p < 0.05 in all) in muscle strength by 26% from baseline (assessed by MMT-8), endurance by 135% from baseline (assessed by FI-2), stability by 11% from baseline (assessed by FVA), and reduced disability by 39% from baseline (assessed by HAQ), which was clinically meaningful in a substantial proportion of patients [ 31 ]. In contrast to another recent study from our group where we described a significant decrease in plasma levels of Hsp90 from baseline to 24 weeks in the CG (baseline: 15.7 [9.8–29.5], week 24: 12.9 [9.7–16.6] ng/mL, p = 0.042) [ 20 ], in the present study we observed a stabilization of the plasma Hsp90 levels over 24 weeks in the IG (baseline: 12.5 [8.9–16.8], week 24: 12.0 [8.0–16.1] ng/mL, p = 0.969; difference between IG and CG: p = 0.014) ( Figure 1 A). Of particular interest, the change in plasma Hsp90 in the IG over the first 12 weeks was able to predict the improvement in muscle endurance (FI-2) over the entire 24-week intervention period (r = 0.510, p = 0.008) ( Figure 1 B).…”
Section: Resultscontrasting
confidence: 99%
“…It is also worth mentioning that the longitudinal IIM cohort with established disease from that study was further analyzed in this study and served as the control cohort for the IIM IG, as originally designed in our 24-week exercise intervention study [ 31 ]. In the CG of this study, although we did not find any significant changes in the mean serum levels of LD and CK at week 24 compared to baseline after continued immunosuppressive therapy (LD: −9%, p = 0.897; CK: +5%, p = 0.154) [ 20 ], we observed a significant increase in IL-2 and IL-6 and a significant decrease in IL-9, MIP-1β, MCP-1, RANTES, and TNF. Meanwhile, systemic levels of all of these cytokines have been shown to correlate with several IIM-specific features [ 33 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations